Computation reduction for turbo decoding through window skipping. Issue 3 (1st February 2016) - Martina, M.; Condo, C.; Roch, M.R.; Masera, G.
Abstract : A simple and effective technique to skip the computation of reliable portions of a frame (windows) for turbo code decoding is proposed. The proposed criterion relies on a very simple approximation of cross‐entropy measure by means of thresholding. This criterion features negligible complexity and low‐memory requirements. Simulation results show that, in the best case, up to 20% of windows can be skipped with no error‐rate degradation. Such a significant computation reduction can be exploited to directly reduce the power consumption as well.